Shaping the Labor Market of Vietnam in the Age of Artificial Intelligence: Comparative Insights from the European Union - Pham, Hong Nhung; Tran, Thi Thuy Lam (Hasanuddin Law Review, 2025)
The right to work has always been a fundamental right of human which was recorded in law documents. However, the recent development of Artificial Intelligence (AI) has created an issue that it may affect the domestic and international labor markets. In Vietnam, where over half of the population participates in the labor force, the rapid advancement of artificial intelligence (AI) is poised to significantly reshape both employment dynamics and the regulatory landscape. While AI presents opportunities to create new types of employment, it simultaneously threatens to displace existing jobs, particularly among low-skilled and vulnerable workers. Despite the growing relevance of this issue, scholarly engagement with the implications of AI for Vietnam’s labor market remains sparse, especially in terms of legal and policy responses. Existing studies tend to focus on economic forecasting or technological development, with minimal attention paid to how labor laws and regulatory frameworks should evolve to address the disruptive potential of AI. This study aims to fill that gap by addressing two central questions: (1) What is the nature and extent of AI’s impact on the Vietnamese labor market? and (2) Which categories of workers are most susceptible to disruption? Through a legal-analytical and comparative approach—drawing insights from the European Union’s labor policy experience—this research offers a novel contribution to the emerging discourse on how Vietnam can construct a forward-looking and socially responsive labor regulatory framework in the age of AI. Empirical methods will be applied to examine the labor statistics of the country. At the same time, the paper will analyze the same phenomenon in the European Union and provide a solution for Vietnam. The analysis revealed that AI in the near future will have a positive effect on the workforce of Vietnam, but at the moment, workers without training are being most affected by its emergence. Thus, this study suggests that Vietnam improves its policy in labor law and social security in order to fully protect the right of all employees.